Characteristics of hardware failure in patients undergoing surgical stabilization of rib fractures: A Chest Wall Injury Society multicenter study. Issue 6 (December 2019) - Sarani, Babak; Allen, Rebecca; Pieracci, Fredric M.; Doben, Andrew R.; Eriksson, Evert; Bauman, Zachary M.; Gupta, Puneet; Semon, Greg; Greiffenstein, Patrick; Chapman, Alistair J.; Kim, Brian D.; Lottenberg, Lawrence; et al.
Abstract : BACKGROUND: Surgical stabilization of rib fractures (SSRF) is increasingly used for severe rib fractures/flail chest. There are no reports discussing mechanisms of failure of implanted hardware, its clinical presentation, or consequences. The purpose of this study was to evaluate the incidence, presenting signs, and clinical sequela of hardware failure after SSRF. METHODS: A multicenter, retrospective study was performed by a group of surgeons with a large SSRF case volume. All cases with known hardware failure from January 1, 2010, to December 31, 2017, were included. The surgeon's experience at the time of hardware implantation, specific implant used, number of failures the surgeon had experienced with the same system, and time from implantation to hardware failure were recorded. Additionally, patient demographics, including age, comorbid conditions, and number and location of rib fractures were recorded. Symptomatology associated with hardware failure and need for explant and/or reimplantation of hardware was also recorded. Nonparametric statistical tests were used to compare cohorts. RESULTS: Of 1, 224 patients who underwent SSRF, 38 patients with 233 rib fractures and 279 fracture segments experienced hardware failure and were enrolled in the study. Twelve patients presented more than 3 months following injury. Median age was 54 years old and 34% were active smokers. One hundred forty-four plates were implanted with a median of four plates per patient. Median number of SSRF cases by each surgeon was 100 (range, 1–280). Fractures and hardware failure were most frequent in the anterolateral/lateral region. Hardware failure was mostly due to screw migration and plate fracture. Hardware failure was asymptomatic in 40% and presented as pain in 42% of cases. Fifty-five percent of the cases required explantation of hardware, and only 10% required SSRF again. There was no difference between the acute and chronic fracture cohorts. CONCLUSION: Hardware failure after SSRF is rare and often asymptomatic. When present, it rarely requires redo SSRF. LEVEL OF EVIDENCE: Therapeutic, level V.